EFFECT OF INTEGRATED INFORMATION TECHNOLOGY ON SUSTAINABLE MOBILITY OF MATATU SACCOS IN NAIROBI COUNTY, KENYA - Muhoro, Priscilla (Journal of Strategic Management, 2021)
Purpose: The purpose of this study was to establish the effect of integrated information technology on sustainable mobility of Matatu Saccos in Nairobi County, Kenya. Materials and Methods: The study was guided by Positivism philosophy while descriptive research design was adopted. The target population was 177 Sacco Managers and two representatives, one from MOT and other from MVOA respectively. The whole population of 179 respondents was used in the study hence; the study employed the census approach. The questionnaire was pilot tested on 18 respondents who were selected randomly. The study applied Cronbach's alpha and the results displayed a high level of internal consistency hence infers that the research tool used in the study was reliable. The data collection instrument was a semi-structured questionnaire, which were dropped and picked later. A semi-structured interview guide was also used. Data was analysed using descriptive and SPSS Version 24. Results: The research findings indicatd that most Saccos have embraced speed-recording devices, vehicle-tracking devices, and that Sacco's were using smartphones. Correlation analysis showed that information technology had a strong positive significant relationship on sustainable mobility of Matatu Saccos in Nairobi County, Kenya (rho = 0.821, p value <0.05). This was confirmed by regression analysis which showed positive and significant influence of integrated information on sustainable mobility (Î² = 1.140, t statistics = 16.582, p value <0.05). This suggested that there is a causal effect of IIT on sustainable mobility. Unique contribution to theory, practice and policy: The research findings indicated that most Saccos have embraced speed-recording devices, vehicle-tracking devices, and that Sacco's were using smartphones. Correlation analysis showed that information technology had a strong positive significant relationship on sustainable mobility of Matatu Saccos in Nairobi County, Kenya (rho = 0.821, p value <0.05). This was confirmed by regression analysis which showed positive and significant influence of integrated information on sustainable mobility (Î² = 1.140, t statistics = 16.582, p value <0.05). This suggested that there is a causal effect of IIT on sustainable mobility.